Customer Feedback Analysis using NLP - Pal, Subhabaha (Indian Journal of Computer Science, 2021)
There are many ways to understand what customers think about certain products: usage surveys, surveys on focus groups, social media mining etc. However, these are time-consuming methods and need enough resources to get useful insights from them. The case is different for Amazon review. It provides a fast, accessible, and vast data resource for getting quick insights. It does both of these things and helps researchers to quickly explore what is going on and the data collection cost is effectively zero. Using NLP techniques on this gathered data provides quick insights into strengths and weakness of products. The paper discusses ways to use NLP in order generate useful insights about the strengths and weakness of a certain product. Apple iPhone 12 Pro Max has been studied here to present the effectiveness of NLP (text analytics) in order to generate useful business insights. In this paper, it has been tried to present an efficient way which helps in obtaining insights from the consumer market like what people look for while buying products and what are the typical causes of frustration in the purchase process or in product. What are the typical pain points / causes of frustration in the purchase process or in a product itself?